Training peer-feedback skills on geometric construction tasks: role of domain knowledge and peer-feedback levels - Alqassab, Maryam; Strijbos, Jan-Willem; Ufer, Stefan (European journal of psychology of education, 2018)
Peer feedback is widely used to train assessment skills and to support collaborative learning of various learning tasks, but research on peer feedback in the domain of mathematics is limited. Although domain knowledge seems to be a prerequisite for peer-feedback provision, it only recently received attention in the peer-feedback literature. In this study, preservice mathematics teachers (N = 43) were involved in a peer-feedback training in which they evaluated geometric construction tasks and were (a) trained to provide peer feedback on different levels (i.e. task, process and self-regulation) and (b) scaffolded with worked examples, feedback provision prompts and evaluation rubrics during the training. A quasiexperimental mixed design was implemented with domain knowledge as the betweensubject factor and measurement occasion as the within-subject factor. Students' peerfeedback provision skills and their beliefs about peer-feedback provision were measured before and after the training. Students with high and medium domain knowledge provided more peer feedback at the self-regulation level, whereas those low in domain knowledge provided more peer feedback at the task-level after the training. Students' beliefs about peerfeedback provision became less positive after the training, regardless of the level of their domain knowledge.